Learning Outcomesʹ Assessment in Virtual Classrooms - DINCĂ, Melinda (Presa Universitară Clujeană, 2022)
The Learning Outcomes’ Assessment in Virtual Classrooms is an open educational resource (OER) consisting of a systematic literature review about the learning outcomes assessment practices, methods, and tools in virtual education environment. The book is based on more than 150 scientific articles and books, with a half being published in the last 5 years (2018-2022), presenting theories, reviews meta-analysis, empirical research results, recent developments and practical experiences of online assessment approaches in the learning process of virtual classrooms. The first chapter approaches the differences and similarities between HE learning settings with various degrees of virtually components; methods and practices of learning outcomes’ assessment. The second chapter identifies innovative practices and methods from complementary perspectives of teachers, selfreflective and peer-reflective assessment of the development of transversal competencies. The third chapter follows the constructivist approach and presents models of authentic learning designs, the role and impact of the practical dimension of bringing real-life cases in the learning process of higher education students.